Marketing Public Relations Live Streaming: Case Study on Building Brand Awareness for Browie Products - Nurhasanah; Dedet Erawati (Indonesian Journal of Business Analytics, 2026)
The development of digital technology has transformed marketing communication practices, particularly through the use of Live Straming on social media. Live Streaming enables teo-way communication between brands and audiences, thereby strengthening Marketong Public Relations (MPR) strategies in building Brand awareness. This study aimns to examine the use of Live Streaming as an MPR stratey by browie in creating brand awareness among young consumers. This research employs a qualitative approach using a case study method. The analysis is grounded in the Marketing Public Relations theory proposed by Harris (1998), specifically the concepts of pull strategy, push strategy, and pass strategy, as well as the Brand awareness theory bu Keller (1993), which includes brand recognition, brand recall, top-of-mind awareness. The study utilized observation as its mode of data gathering of the TikTok account @browie_official, detailed interviews with the management team, and live streams hosts, and also Browie audience, and other supporting documentation. It is evident from the findings that Browie Live Streaming activities also are not exclusively directed at making a sale but also serve as communication space which induces audience engagement and trust. Product demonstrations and association, and position it self as a leading Edge in a specific product category. This study concludes that Live Streaming serves as an effective MPR instrument for local brands to build sustainable Brand awareness in the digital environment.